2015
DOI: 10.1021/acs.nanolett.5b04549
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable Fully-Printed CNT-Based Electrochemical Sensors and Biofuel Cells: Combining Intrinsic and Design-Induced Stretchability

Abstract: We present the first example of an all-printed, inexpensive, highly stretchable CNT-based electrochemical sensor and biofuel cell array. The synergistic effect of utilizing specially tailored screen printable stretchable inks that combine the attractive electrical and mechanical properties of CNTs with the elastomeric properties of polyurethane as a binder along with a judiciously designed free-standing serpentine pattern enables the printed device to possess two degrees of stretchability. Owing to these syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
277
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 295 publications
(278 citation statements)
references
References 51 publications
1
277
0
Order By: Relevance
“…[171] In detail, stretchable components such as PU, ecoflex, and stretchable resistive inks (CNT and Ag/AgCl ink) were printed in a serpentine design array on a textile substrate and modified with ion selective membranes (Figure 6c His team further built a CNT based electrochemical sensor and biofuel cell (BFC) that can endure strains as high as 500% with no effect on structural integrity and sensor performance (Figure 6d). [67] Electrochemical characterization of the device revealed that repeated strain (from 0% to 500%), torsional twisting (180° for 50 cycles) and indenting stress (5 mm depth for 50 repetitions) had negligible effect on its device properties as shown in Figure 6e. A CNT-based device functionalized with selective ionophores and enzymes was developed to realize a wide-range of applications toward potentiometric ammonium sensor ((0.1-100) × 10 −3 m), amperometric enzyme based glucose sensor ((0-10) × 10 −3 m), enzymatic glucose BFC and self-powered biosensor (Figure 6f).…”
Section: Wearable Electrochemical Sensorsmentioning
confidence: 99%
See 4 more Smart Citations
“…[171] In detail, stretchable components such as PU, ecoflex, and stretchable resistive inks (CNT and Ag/AgCl ink) were printed in a serpentine design array on a textile substrate and modified with ion selective membranes (Figure 6c His team further built a CNT based electrochemical sensor and biofuel cell (BFC) that can endure strains as high as 500% with no effect on structural integrity and sensor performance (Figure 6d). [67] Electrochemical characterization of the device revealed that repeated strain (from 0% to 500%), torsional twisting (180° for 50 cycles) and indenting stress (5 mm depth for 50 repetitions) had negligible effect on its device properties as shown in Figure 6e. A CNT-based device functionalized with selective ionophores and enzymes was developed to realize a wide-range of applications toward potentiometric ammonium sensor ((0.1-100) × 10 −3 m), amperometric enzyme based glucose sensor ((0-10) × 10 −3 m), enzymatic glucose BFC and self-powered biosensor (Figure 6f).…”
Section: Wearable Electrochemical Sensorsmentioning
confidence: 99%
“…Sensors in the form of a stretchable capacitor can sense the tensile stretching and normal pressure based on the dimensional change and sense the approaching of an object based on the disturbed fringing field, as shown in Figure 4d. [25,41,43,165] Resistive sensors that can detect various mechanical stimuli such as pressure, [67] Copyright 2016, American Chemical Society. g) Optical images of the integrated watch type gas monitor based on intensive pulsed laser reduced rGO (IPL-RGO) (left) and the resistance change of the rGO sensor when exposed to 20 ppm.…”
Section: Wearable Multifunctional Sensorsmentioning
confidence: 99%
See 3 more Smart Citations